Pemasangan Gratis, Kualitas Jaringan, dan Perilaku Pembelian Indihome pada Gen Z dan Milenial - Siti Nurzanah; Leni Cahyani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The rapid advancement of information technology has significantly increased the demand for fast and reliable internet services, particularly among Generation Z and millennials. To meet this demand, PT Telekomunikasi Seluler (Telkomsel) implemented a marketing strategy by offering a free installation program and improving network quality to attract IndiHome users in the Gen Z and millennial segments. This study aims to examine the extent to which the free installation program and network quality influence purchasing behavior of IndiHome services among Generation Z and millennials. A quantitative approach was employed using a survey method involving 100 respondents in the West Java region. The results indicate that both factors free installation and network quality have a positive and significant effect on purchasing behavior. Among the two, network quality emerged as the most dominant factor influencing purchasing decisions within the Gen Z and millennial groups. Based on these findings, it is recommended that Telkomsel continue to improve its network quality while designing promotional strategies that align with the characteristics and preferences of younger generations to enhance purchase intention and maintain customer loyalty.